Bag Charm dari Kawat Bulu - Muhammad Yasin; Riski Himawan; Melinda Wirastiti; Verinda Yelanita (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
Bag charm is a fashion accessory that is on the rise because of its ability to beautify the appearance of the bag and provide a unique personal touch. In recent years, these accessories have become a significant trend in the fashion world, especially thanks to the influence of social media such as TikTok and Instagram. One of the interesting innovations of bag charm is the use of bristle wire (pipe cleaner) as the main material, which allows the creation of various interesting shapes such as flowers, animals, and funny characters. The business proposal "Bag Charm from Feather Wire" offers creative products with high aesthetic value and personalized appeal according to customer taste. In addition to being easy to make, this product has low production costs and promising profit potential. The theoretical study in this proposal includes the concept of entrepreneurship, product innovation, and market analysis as an important foundation in business development. Marketing strategies through social media and craft exhibitions are also key in expanding market reach. This venture not only provides profitable business opportunities, but also encourages creativity in the handicraft industry and becomes a means of self-expression for consumers. With the wide market potential and uniqueness of the product, the bag charm of bristle wire can become a new trend in the world of handmade accessories.